2015
DOI: 10.4103/0972-4052.161566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hanau's formula in determination of lateral condylar guidance: A clinical research study

Abstract: Statement of Problem:The accuracy and reliability of the methods used for programming the semi-adjustable articulators determine the accuracy in occlusion. The current recommended average settings using the Hanau's formula commonly used by clinicians is questionable, and thus reassessment is needed. This study was carried out to evaluate and compare the lateral condylar guidance: (1) Using the Hanau's formula and the computerized jaw tracking device (Kinesiograph). (2) On the right and left sides using both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The LCG values through kinesiograph were obtained by a mathematical equation based on the trigonometric principle. [ 9 ] Celar and Tamaki demonstrated significant differences between articulator setting and Cadiax compact measurement and concluded that Cadiax compact had reasonably accurate LCG for clinical application. [ 17 ] Hernandez et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCG values through kinesiograph were obtained by a mathematical equation based on the trigonometric principle. [ 9 ] Celar and Tamaki demonstrated significant differences between articulator setting and Cadiax compact measurement and concluded that Cadiax compact had reasonably accurate LCG for clinical application. [ 17 ] Hernandez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose condition contraindicates radiographs refused to give informed consent, and with severely resorbed alveolar ridges were excluded from the study. [ 9 ] Basic information about the study was explained in brief to the patient.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%